Corporate Liability and Legal Protection for Ride-hailing App Drivers for Consumer-Initiated Order Cancellations - Dwi Tatak Subagiyo; Hari Wibisono (APPTHI, 2026)
The rapid expansion of digital platform services has transformed transportation and food delivery transactions, creating new legal challenges regarding the allocation of responsibility among platform operators, consumers, and drivers. Through its Go-Food feature, Go-Jek enables consumers to purchase food while drivers initially bear the purchase costs, making them vulnerable to financial losses resulting from consumer-initiated order cancellations and fraudulent transactions. Despite the growing prevalence of such disputes, the legal protection available to platform-based drivers and the extent of platform liability remain insufficiently addressed within Indonesia’s regulatory framework. This study examines the corporate liability of PT Go-Jek Indonesia and evaluates the legal protection afforded to drivers under Indonesian law. Using a qualitative legal research design with a conceptual approach, the study analyzes primary legal materials, including the Civil Code, Law Number 8 of 1999 on Consumer Protection, and Law Number 22 of 2009 on Road Traffic and Transportation, supported by relevant secondary sources. The findings indicate that fault-based liability under Articles 1365–1367 of the Civil Code provides a legal basis for holding PT Go-Jek Indonesia accountable when drivers incur losses beyond their control. Furthermore, contractual clauses that shift operational risks entirely to drivers are inconsistent with the principles of fairness and good faith. The study recommends strengthening platform governance through compensation mechanisms, enhanced transaction verification systems, and regulatory reforms that explicitly address digital platform transactions. These measures are expected to improve legal certainty, strengthen the protection of platform-based drivers, and promote greater trust in Indonesia’s digital economy.